Knowledge attitudes and practices of nursing services staff Colombo South General Hospital on HIV infection / AIDS. - Sabaratnam, S. D (My University, 1995)
240 staff nurses from the Colombo south general hospital were interviewed to assess whether they have adequate knowledge,positive attitudes and good practices to care for HIV infection/AIDS patients without fear and prejudice.Two group,the recently passed out nurses(less than 10 years work experience) and older nurses(more than 10 years work experience) were compared to see whether there was significant difference in their knowledge,on HIV infection/AIDS.It was found that the overall knowledge on HIV infection/AIDS was inadequate.But the younger nurses were significantly better than the older nurses.p0.05.Most of the nurses had negative attitudes towards HIV/AIDS patients,their rights and ethical issues.There was no significant difference between the younger and older nurses in their attitudes. Younger nurses were biased by older nurses attitudes and social prejudices.Practice of universal precautions were poor among all nurses with no significant difference between the two groups.Nurses attributed this lack to unavailability of masks gowns and gloves.